Menggugat Eksklusivisme Umat Pilihan Allah: Tafsir Ideologi terhadap Ulangan 7: 1-11 dan Yohanes 14: 6 dalam Konteks Kemajemukan Masyarakat - Edward Jakson Turalely; Olivia Joan Wairisal; Fiktor Fadirsair (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2022)
Violence and conflict in the name of religion have increased in Indonesia, including Maluku. Social strife in Maluku provides evidence of the reality of an objectionable and properly managed society. Conflict in the name of religion has contributed to legitimization with bible texts, including Deuteronomy 7: 1-11 and John 14: 6. Therefore, this article is the result of re-interpretation utilizing ideological criticism of these biblical texts. Through the interpretation, the authors found that the exclusive narrative of Deuteronomy 7: 1-11 and John 14: 6 was influenced by the social, political, and economic situation. Thus, both texts need to be reinterpreted contextually regarding the plurality of Indonesian society. In the end, this article emphasizes that the concept of God's people cannot be interpreted exclusively but refers to all humankind universally.